El portafolio académico como estrategia didáctica para mejorar el aprendizaje de las funciones cuadráticas en los estudiantes del primer año de bachillerato general unificado paralelo C de la unidad educativa Calasanz, de la ciudad de Loja, período académico 2013-2014 - Sigcho Granda, María Fernanda (2015)
The research entitled the academic portfolio as didactic strategy for improving the learning of quadratic functions in students in the first year of baccalaureate general unified parallel C at Unidad Educativa Calasanz, of Loja city. 2013- 2014 academic year. aims to use the academic portfolio as a teaching strategy to enhance learning of quadratic functions This work responds to a design pre-experimental because it works with a control group; for the compliance of the proposed objectives were used methods such as comprehensive analytic-synthetic, deductive and scientific that arose in the following order: understanding, diagnosis, modeling, application and assessment of the effectiveness, which led to employ instruments such as surveys of diagnosis on the learning of q quadratic functions, pre test, post test and workshops for implementing academic portfolio as a teaching strategy; to determine the effectiveness of the alternative, worked with a teacher and thirty-five students at Unidad Educativa Calasanz. The results of which are exposed in this thesis. The major findings in the present investigation were difficulties, shortcomings or cognitive needs in the optimization of learning of quadratics functions, the same that can reduce or mitigate the use of academic portfolio as a teaching strategy.